Hubungan Pemberian ASI Eksklusif Dengan Pertumbuhan Dan Perkembangan Pada Bayi Usia 6-12 Bulan Di Wilayah Kerja Poskesdes Pangururan Kabupaten Toba Samosir Tahun 2023 - Dewi Juliani Simanjuntak; Nopalina Suyanti Damanik; Eka Falentina Tarigan; Eka Purnama Sari (Jurnal Siti Rufaidah, 2024)
The United Nation Children's Fund (UNICEF) and the World Health Organization (WHO) recommend that children should be breastfed only with breast milk (ASI) for at least six months. Solid food should be given after the child is 6 months old, and breastfeeding should be continued until the child is two years old (WHO, 2020). This study aims to analyze the relationship between exclusive breastfeeding and growth and development in babies aged 6-12 months in the Pangururan Health Post Work Area, Toba Samosir Regency in 2023. This research is correlational with a cross sectional approach and bivariate data analysis is the data analysis used in the research to determine the relationship or influence of the independent variable with the dependent variable using Chi Square analysis with a significant p-value (0.05) (Hardani, 2020) Based on the research results. Based on the results of statistical tests using Chi-Square, exclusive breastfeeding was obtained with growth in babies aged 6-12 months in the Pangururan Health Post Work Area, Toba Samosir Regency in 2023 with a p-value of 0.000. Providing Exclusive Breastfeeding with Development in Babies Aged 6-12 months in the Pangururan Health Post Work Area, Toba Samosir Regency in 2023 with a p-value of 0.000 This means that there is a relationship between exclusive breastfeeding and growth and development in babies aged 6-12 months in the working area of ​​the Pangururan Village Health Post, Toba Samosir Regency in 2023